Preliminary Yield Test of Sweetpotato Promising Clones Rich in Potassium - Febria Cahya Indriani; Joko Restuono; Wiwit Rahajeng; Purwono (Future Science, 2021)
Sweet potato is one of the food commodities that prospective for food diversification and export. Another potential is its high nutritional content so it is useful as a healthy functional food, Potassium content in sweetpotato is known good for human health. The objective of this research was to obtain the information about yield and morphological characteristics of the promising clones of sweetpotato with rich in potassium. The research was carried out in Paras village, Poncokusumo, Malang district, East Java, at dry season I in 2019. The 40 promising clones including four check varieties were arranged in randomized block design with three replications. The results showed that there was a significant effect of clones on the observed variables. The tuber weight variable per plot showed a range of 9.07 -26.93 kg/plot, there were about twenty clones that had tuber weight more than check varieties that is Kidal, Beta 2 and Antin 2. Based on the morphological characters of the tubers, the promising clones selected generally had the colour of orange flesh.